2006
DOI: 10.1097/01.tp.0000209439.27719.ed
|View full text |Cite
|
Sign up to set email alerts
|

Combined CMV Prophylaxis Improves Outcome and Reduces the Risk for Bronchiolitis Obliterans Syndrome (BOS) after Lung Transplantation

Abstract: In CMV high risk patients, additional CMV-IG administration seems to be effective to reduce CMV-related morbidity and to avoid CMV-related mortality. Reduced incidence of BOS may result from improved CMV prevention, although randomized trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
64
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 23 publications
5
64
1
Order By: Relevance
“…In fact, several studies have reported the successful prevention of CMV disease in high-risk transplant recipients using passive immunization [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several studies have reported the successful prevention of CMV disease in high-risk transplant recipients using passive immunization [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Monotherapy with IV GCV has clearly delayed the incidence of CMV infection, disease and subsequent BOS. 6 -8 Combination therapy with IV ganciclovir and CMV-IVIg for short-term prophylaxis further reduces the incidence of CMV disease 9,10 and was recently demonstrated by Ruttman et al 11 to improve rates of CMV disease, 3-year freedom from BOS and survival in high-risk allograft recipients of CMV-positive donors. A study by Zamora et al 12 further showed protracted therapy with valganciclovir for at least 6 months and up to 1 year reduces incidence of CMV disease to as low as 2.3% in CMV-seronegative LTRs of CMV-positive donors.…”
mentioning
confidence: 94%
“…Most immunosuppressive and anti-infective drugs have only been proven for safety and efficacy in kidney or liver transplant recipients. Therefore, no clear recommendations concerning prophylactic regimen and dosage in cardiothoracic transplantation are available from the companies distributing CMV-IG (19,20). In the following pages we'll try to review the role CMV on lung transplantation and the possible best approach to its management.…”
Section: Introductionmentioning
confidence: 99%